FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN DIET DIABETES MELITUS PADA LANSIA - Rosdiana, Rosdiana; Aryatika, Karera; Putra, Windu Unggun Cahya Jalu; Lellu, Amos (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Based on an initial survey, that DM patients who do outpatient care at RSUD Dr. Sayidiman Magetan in 2021 amounted to 264 cases, in 2022 amounted to 656 cases and in 2023 alone amounted to 772 cases. The purpose of the study was to determine the factors associated with diabetes mellitus diet compliance in the elderly. The research design used in this study was cross sectional. The research was conducted at Dr. Sayidiman Magetan Hospital. The research was conducted in July 2024. The population was all outpatients with Diabetes Mellitus in the polyclinic of RSUD dr Sayidiman Magetan totaling 65 patients. The sample amounted to 56 respondents. The sampling technique used in this study was purposive sampling. Data analysis was performed univariate and bivariate. The results of the study there is a relationship between attitude (p value: 0.020) and health worker support (p value: 0.045). It is recommended that hospitals can create peer groups, improve therapeutic communication, and carry out counseling activities using audio visuals regarding the importance of adherence to a diabetes mellitus diet. As well as increasing the role of the family in patient assistance so that complications of diabetes mellitus can be prevented.Keywords: Health worker support, diabetes, attitude.